Kinetic Studies in the Oxidation of 2-aryl-3-Hydroxychromenones Using Sodium Hypochlorite (NaOCl) as an Oxidant - Kulvir Kaur; Gurmeet Kaur; Mandeep Kaur; Amandeep Kaur; Manisha Bansal (Challenges and Advances in Chemical Science Vol. 8, 2022)
Oxidation of 3-hydroxy flavone (3-HF) and 3-hydroxy-2-(thiophene-2-yl)-4H-chromen-4-one (THC) with sodium hypochlorite (NaOCl) as an oxidizing agent, has been reported. 3-hydroxy-2,3-dimethoxy-2-phenylchroman-4-one (1a) has been identified as the product of 3-HF in methanol (MeOH ) as solvent, by IR, 1H-NMR and ESI-MS spectroscopic techniques. This product is formed without any side reaction. Yield of this product is close to 100%, which could be calculated by separating the absorption spectra of the product from that of the reaction mixture in situ. On the other hand, by similar oxidation THC gives a dimeric product (2a). A mechanism for the formation of 1a has been given.